Susceptibility of clinical methicillin-resistant Staphylococci isolates to new antibiotics - Oksuz, Lutfiye; Gurler, Nezahat (The Journal of Infection in Developing Countries, 2013)
Background: The treatment of methicillin-resistant staphylococcal infections has been a growing problem both in and out of hospitals for the past 30 years. Therefore, there is a need for other antibiotics as an alternative to glycopeptides in the treatment of methicillin-resistant staphylococcal infections. This study investigated the in vitro susceptibility of 49 methicillin-resistant Staphylococcus aureus (MRSA) and 59 methicillin-resistant coagulase negative staphylococci (MRCNS) clinical isolates to daptomiycin, telithromycin, tigecyclin, quinupristin/dalfopristin, and linezolid. Methodology: The identification of the strains was made by conventional methods. Antibiotic susceptibility tests were performed according to CLSI. Methicillin resistance was determined by cefoxitin disk. Susceptibilities of the strains to daptomycin, quinupristin/dalfopristin, tigecycline, and vancomycin were performed using the E-test according to the recommendations of CLSI 2011 and the manufacturer. Results: Two strains of MRCNS were resistant, and one was teicoplanin intermediate. It was found that one (2%) strain of MRSA and two (3%) strains of MRCNS were resistant to tigecyclin. Telithromycin resistance was detected in 33% of MRSA strains and 37% of MRCNS strains. Inducible clindamycin resistance was found in nine (18.4%) strains of MRSA and eighteen (30.5%) strains of MRCNS. All strains were susceptible to daptomiycin, quinupristin/dalfopristin, and linezolid. Conclusions:Although it has recently been used, telithromycin has a high percentage of resistance; its use for methicillin-resistant staphylococcal strains, therefore, should be limited. Daptomycin and quinupristin/dalfopristin were found to be effective against MRSA and MRCNS strains and were concluded to be a good choice in the treatment of methicillin-resistant staphylococci.